Anchoring perovskite LaMnO3 nanoparticles on biomass−derived N, P co−doped porous carbon for efficient oxygen reduction. (1st June 2018) - Hu, Jie; Shi, Ziwei; Su, Chao; Lu, Benqian; Shao, Zongping; Huang, Hao
Abstract: We propose a new perovskite/carbon composite of LaMnO3 nanoparticles anchored on N and P co-doped porous carbon as an efficient electrocatalyst for oxygen reduction reaction (ORR) in alkaline solution. A facile two-step method is applied for the synthesis of such composite, involving the pyrolysis of cheap, abundant and renewable natural okara with the formation of N and P co-doped porous carbon for the first step, and the deposition of LaMnO3 nanoparticles on the carbon surface by sol-gel synthesis at the second step. A synergistic effect is built between the LaMnO3 nanoparticles and the porous carbon substrate, resulting in obviously improved ORR activity as compared with the individual N, P co-doped carbon and the nanosized LaMnO3 electrocatalysts, in terms of onset potential, limiting current density, and stability. The LaMnO3 /N, P co-doped carbon composites further evaluated as an air electrode in a Zn-air battery, demonstrating attractive performance, including high discharge voltage plateau (∼1.2 V) and excellent stability with negligible degradation in voltage at 25 mA cm −1 discharge current for 24 h. The present results highly promise the LaMnO3 /biocarbon nanocomposite as a potential metal-free ORR electrocatalyst, which may find a wide use in metal-air batteries or fuel cells.